ECONOMIC VALUATION OF USE OF CORAL REEFS IN THE BAYS OF HUATULCO, OAXACA, MEXICO - Robles-Zavala, Edgar; de Yta-Castillo, Diana; Escamilla-Perez, Blanca Edith (Ecosistemas y Recursos Agropecuarios, 2015)
The aim of this study was to determine the recreational use value of three coral reefs in the Bays of Huatulco (Bahías de Huatulco), Oaxaca, Mexico. In total, 263 domestic tourists were interviewed, and their socioeconomic pro????le and perception of the coral reef they visited were determined. Using the contingent valuation method, a willingness to pay $ 48.4 for conservation activities was determined, as well as a net annual benefit from the reef of $18 243 629.40. The results of the study show the high economic potential of the reef ecosystems in Huatulco, which should guide public policy strategies for the conservation and sustainable management of the resource.